Design and synthesis of organic nonlinear optical materials - Zhanabergenova, M.; Baptayev, B.; Tauanov, Z.; Zhakiyeva, Z.; Yergeshbayeva, S.; Berillo, D.; Adilov, S. (Nazarbayev University, 2014)
Following the development of the idea of octupolar molecules as nonlinear optical materials a variety of compounds have been reported. Trans-porphyrins have a great potential to selforder into octupolar symmetry. Nonlinear optical properties can be tuned by using strong donor-acceptor groups in porphyrins as well as extension of conjugation. Here we report the syntheses of trans-A2D2- porphyrins and their dimerization into cubic octupoles by organic bidentate ligands.
Keywords: nonlinear optical; organic; trans-porphyrins; porphyrins; nitrophenyl; analyz; molecules